Analysis of Description of Nurse Breastfeeding Behavior Who Work at Puskesmas Pademawu Pamekasan - Adi Sutrisni; Nurdina Nurdina; Sandu Siyoto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
This research is a qualitative research with case study method to examine the nurse breastfeeding behavior who work at puskesmas pademawu pamekasan. The focus of this study was to explain the behavior of nurses in exclusive breastfeeding to their infants while working in Puskesmas. The purpose of this research is to give a conclusion about nurse motivation factor in exclusive breastfeeding to the baby, to know the husband support and health center policy and nurse strategy in giving exclusive breastfeeding while working in Puskesmas. The data analyzed were interviews with nurses who had successfully provided exclusive breastfeeding, husband and head of Puskesmas. Population in this research is Nurses who succeed to give exclusive ASI as much as 37 people at Pademaku Pamekasan Health Center while the sample taken is 15 people taken by purposive sampling The results showed that several factors that influence the exclusive breastfeeding of working nurses is the desire and commitment to continue breastfeeding. In addition, the results showed that family support in providing exclusive breastfeeding is needed by nurses who work. Workplace policy in providing freedom of exchange shift is also a supporting factor. Today many factors that make it easier for mothers to give exclusive breastfeeding even while working. Many techniques and ways to keep the baby breastfeeded even though the mother works, one of them using a package of electric pumps complete with breast milk box for breastfeeding storage. Breast pump can be done in place of working mother then delivery to their home so that a baby can drink milk according to time. In addition, the information about exclusive breastfeeding problems while working can be accessed through social media or the media breastfeeding mothers group by What Apps Group. This makes it easier for mothers to get a solution of the problems at hand.